2013
DOI: 10.1155/2013/862312
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of Preventive Measures for Glucocorticoid-Induced Osteoporosis among Veterans with Inflammatory Bowel Disease

Abstract: Purpose. We examined current osteoporosis prevention practices in patients with inflammatory bowel disease (IBD) on chronic steroid using the 2003 American Gastroenterological Association guidelines as standard of care. Methods. We identified all IBD patients followed at the Oklahoma City VA Medical Center from January 2003 to December 2010, who had been on daily oral steroids (prednisone ≥5 mg or budesonide ≥6 mg) for ≥3 consecutive months. Associations of calcium and vitamin D (vitD) prescribing and bone min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Additionally, the present review found that adherence to guideline-recommended therapies to prevent fracture remains low, likely due to low awareness. 12 Further research on how to accelerate the adoption of such prevention guidelines can greatly reduce the osteoporotic risks induced by corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the present review found that adherence to guideline-recommended therapies to prevent fracture remains low, likely due to low awareness. 12 Further research on how to accelerate the adoption of such prevention guidelines can greatly reduce the osteoporotic risks induced by corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that, among certain populations, low, yet increasing, adherence to osteoporosis guidelines (eg, prescribing of calcium and vitamin D in long-term corticosteroid users) over the past decade have been observed. 12 Teriparatide, oral bisphosphonates, and physician education for improved management may be costeffective in specific populations in the prevention of glucocorticoid-induced osteoporosis. [13][14][15]40 It is important to determine methods of improving adherence to prevention guidelines via health system and health policy research.…”
Section: Corticosteroid Treatment Guidelinesmentioning
confidence: 99%
“…Glucocorticoid therapy used in treating autoimmune diseases, such as inflammatory bowel disease (IBD) and systemic lupus erythematosus (SLE), could lead to osteoporosis . IBD patients are known to have elevated proinflammatory circulating cytokine and increased risk of fracture .…”
Section: Mirnas In Secondary Osteoporosismentioning
confidence: 99%
“…Some of these may be potentially beneficial, but the majority are possibly detrimental. Interactions may even occur between more than two drugs simultaneously 8,9,10 . We pursued to determine the frequency of diverse patterns of asthma controller medication in the tangible clinical practice 11 .…”
Section: Introductionmentioning
confidence: 99%